THE EFFECT OF THE EUCLIDEAN GEOMETRY SHORT LEARNING PROGRAMME USING THE WORKED-OUT EXAMPLES TEACHING APPROACH ON MATHEMATICS TEACHERS' PERFORMANCE - Rabaza, Msebenzi; Hamilton, Joleen (JOHME: Journal of Holistic Mathematics Education, 2022)
The studies on the worked-out examples teaching approach (WOETA) have been investigated globally and in South Africa, showing gains in learners' performance. This study reports on the Euclidean geometry short learning programme (EGSLP), which used worked-out examples teaching approach (WOETA) intervention to secondary mathematics teachers enrolled in one university campus in the Free State province. This study used one group pretest-posttest research design.65 participants completed the pre-test, participated in WOETA, and later completed the post-test. The WOETA engaged the participants in the Euclidean geometry six topics, straight-line geometry, classification of triangles, Pythagoras, similarity and congruency, properties of polygons, and measurement that helped them to acquire procedural and conceptual knowledge. The findings revealed that the WOETA improved the participants' performance in two topics, straight-line geometry and classification of triangles. In contrast, it failed in four topics Pythagoras, similarity and congruency, properties of polygons, and measurement. Cronbach alpha was used to calculate the reliability of the pre-test and was 0,52, while the post-test reliability was 0.30, and these values were deemed not acceptable and not reliable. The findings also revealed that the WOETA does not affect participants' Euclidean geometry performance.